Food court management system / Muhammad Alif Rusyaidi Abdul Rashid and Alif Faisal Ibrahim - Abdul Rashid, Muhammad Alif Rusyaidi; Ibrahim, Alif Faisal (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Food court is an essential section in a huge building because people can chill while fill their stomach with various type of cuisine. Moreover, it become important because everybody need to eat in order to gain energy from the food consumption. Due to the fact that food court is a place that will be visit by many people that intended for dining, it will be filled with people and further cause a crowd. Thus, Food Court Management System was developed in order to reduce the crowd in the food court. There are two objective of this research which to develop a Food Court Management System that suits any personal device by using a web-based system that will manage the ordering process in the food court followed by to test the functionality and the usability of the system whether it ease the user for ordering process purpose. For the methodology, this research utilized the agile model that consist of five phases including planning, analysing, design and implementation, testing and end with maintenance. In order to realise this research, two different software has been used to develop the system which are Visual Studio Code and XAMPP control panel. Apart from that, for the testing phase will be carried out the functionality and usability testing then the result will be analysed based on the graph. The user mostly agreed on this system is learnable and satisfied with the system. Finally, the users concurred that this web-based system is organised properly.